Disaster governance and hybrid organizations: accounting, performance challenges and evacuee housing - Sargiacomo, Massimo; Walker, Stephen P (Accounting, auditing & accountability journal, 2022)
PurposeThe purpose of this paper is to investigate how public/private hybrid and ambiguous organizations played pivotal roles in a governmental programme of housing reconstruction following a major earthquake in central Italy in 2009. Venturing beyond the boundaries of institutional isomorphism and using a Foucauldian approach, the longitudinal analysis seeks to illuminate accounting and performance challenges and provide insights to the calculative techniques associated with evacuee housing.Design/methodology/approachIn “act 1” this paper investigates the role of a consortium created during the recovery stage of the disaster to construct temporary housing. In “act 2” attention shifts to consortia established for the reconstruction of buildings in devastated communities. The total observation period is 11 years. 31 semi-structured interviews were conducted with 15 key-actors. A broad range of official documents was also consulted.FindingsIn the immediate aftermath of the earthquake a comprehensive reporting system was established to facilitate the construction of 19 new towns for 15,000 evacuees. The mix of accountants, engineers and architects who developed the system and a building prototype evidences the assembly of diverse calculative techniques by different experts and the de-territorialization of subject disciplines. During reconstruction technologies of government included the introduction of standardised systems and vocabularies that homogenised administrative procedures among diverse experts.Research limitations/implicationsThis paper provides academics and policymakers with insights to accounting, performance management and accountability in hybrid organizations in the largely unexplored realm of post-disaster evacuee housing. Further studies are needed to examine the politics of calculation in similar contexts.Originality/valueThis paper fills a gap in the literature by exploring the role played by individual experts working for hybrid organizations. Further, by exploring actual practices over an extended period of post-disaster recovery and reconstruction, the study highlights how experts intervened to solve problems at the meso-political level and at the micro-organizational level.